2022
DOI: 10.2196/38541
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of Internet-Based Communication for Public Health: Systematic Review

Abstract: Background Communicating strategically is a key issue for health organizations. Over the past decade, health care communication via social media and websites has generated a great deal of studies examining different realities of communication strategies. However, when it comes to systematic reviews, there is fragmentary evidence on this type of communication. Objective The aim of this systematic review was to summarize the evidence on web institutional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 97 publications
0
1
0
Order By: Relevance
“…Our model reflects the current assumption that engagement with the campaign is the focal point, with all outcomes dependent on generating engagement. Others have also noted how frequently engagement is reported in evaluations [ 118 ], and determining what content generates engagement is a frequent subject of research [ 119 , 120 ]. When considered alongside our findings, this suggests that engagement is sometimes seen as the ultimate goal of campaigns rather than an intermediate step to achieving health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Our model reflects the current assumption that engagement with the campaign is the focal point, with all outcomes dependent on generating engagement. Others have also noted how frequently engagement is reported in evaluations [ 118 ], and determining what content generates engagement is a frequent subject of research [ 119 , 120 ]. When considered alongside our findings, this suggests that engagement is sometimes seen as the ultimate goal of campaigns rather than an intermediate step to achieving health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…16 Governments have employed a variety of strategies designed to debunk misinformation, including monitoring and fact-checking, economic incentives and legislative policies. [17][18][19][20] These strategies must be assessed and compared in terms of impacts and effects on health outcomes and behaviour change. For instance, one older evidence synthesis found that correcting misinformation has a moderate influence on belief in misinformation, rebuttals are more effective than forewarnings and appeals to coherence are more effective than factchecking and appeals to credibility.…”
Section: Open Accessmentioning
confidence: 99%